Knowledge, attitude and practices towards anemia among late adolescent girls of JSS schools and colleges of Mysuru, India: a cross-sectional survey - Verma, Satendra Kumar; Khanum, Rufia Shaistha; Kumar, Sunil D.; M. R., Narayanmurthy (International Journal Of Community Medicine And Public Health, 2021)
Background: Anemia is a serious issue globally affecting all age groups. Anemia can be both acute and chronic. The most common cause is undernutrition which is a common issue in underdeveloped countries. Knowledge about anemia, attitude, and practices are important to decrease the burden of anemia. The community should be educated about the causes and prevention of anemia. Despite various measures like WIFS, POSHAN abhiyan, and National iron plus initiative, etc., there is still a long way to go to improve the nutritional status of adolescents and curb nutrient deficiency disorders. Methods: A cross-sectional study was conducted in JSS schools and pre-university during February 2021. The sample size was 292, but a total of 300 girls in the late adolescent age group were included in the study. A structured proforma was used to collect data regarding knowledge, attitude, and practices towards anemia. Descriptive statistics such as mean, frequencies, and percentages were calculated. Results: Mean age of the participants was 16.8±1 years. The knowledge about anemia was poor, positive attitudes and good practices were noticed among the participants. Conclusions: Anemia is a huge problem among adolescent girls. The awareness is poor regarding the disease and its effects. The community is ignorant about the detrimental effects of anemia. Hence appropriate health interventions targeting women and children are needed to see any positive changes in their status.